Building resilient cattle through better management of buffalo health - Alfredo Sánchez; Merilio Montero (Revista Científica)
Livestock has been involved among the causes of environmental deterioration due to the felling of forests, soil degradation, the affectation of water resources, and greenhouse gas (GHG) emissions. The high proportion of damage attributed to the live-stock sector is debatable compared to other sectors inherent to human development. However, it is unquestionable that immediate action is required to address the global environmental situation. The most effective way to stop it is to reduce methane, but it is not the only way. This refers to producing food through more sustainable, friendly models, less dependent on external inputs, with low energy consumption and reduced GHG emissions, but at the same time with better yields (productive and reproductive) and high efficiency. It is necessary to implement sustainable buffalo production systems through a planning process, which includes efficient technologies that interact favorably with the environment. The execution of management programs (vegetable, animal, genetic, advanced reproduction, health, well-being, and profitability) must focus on new concepts and strategies that are friendly to the environment. In addition to sustainability and food production, there is a need to maximize the capacities of the buffalo and establish sanitary programs based on and guaranteed a healthy herd and safe production (on the postulate of “one health”). It is necessary to know in depth about the immunobiology of the buffalo and its strategies for controlling pathogens. In particular, the immune system’s effectiveness in recognizing the progression and pathogenic action of some agents, from which the buffalo is not exempt from becoming infected, but which do not thrive or induce clinical manifestations or functionality variations. On the contrary, other acute diseases (clostridial, for example) or those caused by intracellular bacteria may have a reserved prognosis, developing complex pictures. This unique set defines that the buffalo species is not resistant to these diseases But, instead, resistant to many. This condition should be under-stood as the ability to adapt efficiently and recover quickly from stress, adversity, or infection. This resilience must be strengthened through handling strategies and by implementing specific and strategic health plans built on solid foundations of diagnostic structures to promote prevention and contribute to more ethical and rational treatments, stimulating a unique association (environment - pathogen - buffalo). Therefore, interventions do not necessarily have to be done through drugs. Resilience development involves maximizing immunity, based on genetic programs and selection for individual health and product; In health management strategies that strengthen mother/child interaction from birth; In which the colostrum is guaranteed in time and form; In which anthelmintic treatments respond to a rational use on populations with parasitic pathological loads, and that have a minimum environmental impact (on dung insects, grassland ecosystems and edaphic factors), or on the dynamics of the ecosystems; Where the (restricted and cautious) use of antimicrobials prevents the continued proliferation of resistance, nor compromises human health. Build it through genetic improvement for a genotype/environment interaction favorable to the development of optimal immunity; Through the comfort and guarantee of animal welfare; Through rational grazing with low environmental impact, in polyphytic pastures, with shade and minimal use of pesticides. Strengthen the population’s health through strict controls to eradicate diseases such as Brucellosis and Tuberculosis, which will positively impact public health. In a short time, we will have multiple possibilities generated by molecular bioengineering and molecular genetics for identifying and multiplying actual resistance genes to these diseases and others of economic importance that compromise buffaloes. In conclusion, buffalo production and the tropics represent elements with extraordinary potential to generate positive synergies and promote agroecological models that lead to climate change mitigation by promoting carbon storage in the soil and reducing GHG emissions, neutralizing the adverse effects on soils and vegetation and, ultimately, contributing to the regeneration of the ecosystem. However, for it to work, it is necessary to generate a deep knowledge of the animal species, the ecosystem, and the ecological principles of grazing, Capacities that producers must develop.